The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/pa.2125
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial orientation and generic competitive strategies for emerging SMEs: Financial and nonfinancial performance perspective

Abstract: In the competitive markets, business ventures have not only emphasized financial performance but nonfinancial performance has also become the need of the day due to its significant role in increasing customers. However, minor attention is given to the relationship between entrepreneurial orientation, business strategy and nonfinancial performance of emerging small and medium enterprises (SMEs). This study scrutinizes the effect of each dimension of entrepreneurial orientation (i.e., innovativeness, risk‐taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 103 publications
(175 reference statements)
3
48
1
Order By: Relevance
“…The response rate achieved in this research was 50.83%. A similar response rate has been quoted in other studies in the same industry (Anwar, 2018; Anwar & Shah, 2021).…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…The response rate achieved in this research was 50.83%. A similar response rate has been quoted in other studies in the same industry (Anwar, 2018; Anwar & Shah, 2021).…”
Section: Methodssupporting
confidence: 88%
“…EO is the most dominant element for new ventures to upsurge their international performance and gain a competitive position in the marketplace (Clark & Covin, 2021). EO proxies such as risk‐taking, innovativeness, and proactiveness are the most arrogant elements, which help firms to become financially successful in developing countries (Anwar & Shah, 2021; Khan, Salamzadeh, Kawamorita, & Rethi, 2020). When top managers are in favor of entrepreneurial activities, that is, innovative, risk‐taking, and proactiveness, they achieve higher level performance (Linton & Kask, 2017; Semrau, Ambos, & Kraus, 2016; Shirokova, Osiyevskyy, & Bogatyreva, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, technology orientation is measured using a 12-item scale adopted from Gatignon and Xuereb (1997). Moreover, the performance of SMEs is measured using 10 items adopted from Anwar and Shah (2020) and Danso et al (2016). The efficiency of SMEs is measured relative to their main competitors or industry over the last three years (1 = 'extremely declining'; 5 = 'extremely improved').…”
Section: Methodsmentioning
confidence: 99%
“…Pro-activeness improves financial efficiency (Hossain & Al Asheq, 2019) and has an important influence on SMEs (Jalali et al, 2013). Proactive companies gain a strategic edge through customer demands, innovative campaigns and higher charges (Anwar and Shah, 2020). Mahar and Ghumro (2019) indicated that competitive aggressiveness and autonomy are important for the organisational successes of SMEs.…”
Section: Entrepreneurial Orientation and Smes Performancementioning
confidence: 99%
“…Additionally, we focused on the traditional theory of EO where three dimensions are used in the literature (Mason et al, 2015; Miller, 1983). These dimensions are still acceptable in research and provide a complete picture of EO (Anwar & Shah, 2020; Mason et al, 2015). However, the modern theory of EO claims five dimensions; competitive aggressiveness and autonomy as an addition (Dess & Lumpkin, 2005; Lumpkin & Dess, 1996; Shah & Ahmad, 2019; Soriano et al, 2012).…”
Section: Implications For Practicementioning
confidence: 99%